The Role of Information Technology in Improving Resource Management Efficiency in Sustainable Agriculture - Christin Imelda Girsang (Jurnal Minfo Polgan, 2023)
Agriculture is one of the key sectors in the global economy that plays a key role in feeding the world's growing population. However, the agricultural sector is also faced with serious challenges, including climate change, environmental degradation, increasing demand for food, and pressure on natural resources. This research aims to analyse the role of IT in improving resource management efficiency in sustainable agriculture. This research is a literature review that adopts a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that the role of information technology in improving resource management efficiency in sustainable agriculture cannot be ignored. Information technology enables farmers to better manage natural resources, optimise agricultural production, reduce negative impacts on the environment, and face challenges associated with climate change and global markets.